2012
DOI: 10.2217/fvl.12.44
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T cells and Th17 cells in Viral Infections: Implications for Multiple Sclerosis and Myocarditis

Abstract: In immune-mediated diseases, Treg and proinflammatory Th17 cells have been suggested to play either suppressor (beneficial) or effector (detrimental) roles, respectively. Tissue damage in viral infections can be caused by direct viral replication or immunopathology. Viral replication can be enhanced by anti-inflammatory responses and suppressed by proinflammatory responses. However, Tregs could suppress proinflammatory responses, reducing immunopathology, while Th17 cell-induced inflammation may enhance immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 122 publications
0
80
0
1
Order By: Relevance
“…They were reported to be involved in accelerating the severity and incidence of collagen-induced arthritis (CIA) and in perpetuating the disease progression (19). But recently, they were reported to alleviate many autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE) (18) and systemic lupus erythematous (13). It is still not understood why iNKT show converse functions in different autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were reported to be involved in accelerating the severity and incidence of collagen-induced arthritis (CIA) and in perpetuating the disease progression (19). But recently, they were reported to alleviate many autoimmune diseases such as experimental autoimmune encephalomyelitis (EAE) (18) and systemic lupus erythematous (13). It is still not understood why iNKT show converse functions in different autoimmune diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, iNKT might theoretically combine functions of both NK and Treg. NK could kill pathogens including virus (15), while Treg could alleviate the immune and inflammatory response (12,13,17), indicating a promising role of iNKT in both virus clearance and immune regulation. In addition, recent reports showed that iNKT had a beneficial effect in various pathologic conditions, such as experimental autoimmune encephalomyelitis (EAE) (18) and systemic lupus erythematosus (1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the balance between regulatory T (Treg) and interleukin-17-producing (Th17) cells has also been suggested to play an important role in the pathogenesis of viral myocarditis. 180 Treg inhibits proinflammatory responses, resulting in reduced immunopathology, whereas Th17-mediated immunity induces enhancement of immunopathology. 180 The adaptive immunity responses begin later in the acute and subacute phases of myocarditis.…”
Section: Immunopathogenesis Of Viral Myocarditismentioning
confidence: 99%
“…180 Treg inhibits proinflammatory responses, resulting in reduced immunopathology, whereas Th17-mediated immunity induces enhancement of immunopathology. 180 The adaptive immunity responses begin later in the acute and subacute phases of myocarditis. Lymphocyte infiltration can aid with the clearance of virus-infected cardiomyocytes, but it may also cause myocardial damage.…”
Section: Immunopathogenesis Of Viral Myocarditismentioning
confidence: 99%
“…In MS patients, lesions are located throughout the central nervous system, including the optic nerve, cerebrum, cerebellum, brainstem, and spinal cord (1). The pathology has complicated associations between T helper 17 cells (Th17), CD4+ and CD8+ T-cells (2), and regulatory T cells (Treg) (3). NMO is characterized by optic neuritis and myelitis (4,5).…”
Section: Introductionmentioning
confidence: 99%